The biological role of magnesium deficiency in violation of homeostasis in women: a literature review - T Yu Pestrikova; E A Yurasova; I V Yurasov (IP Berlin A.V., 2016)
In the literary review presents recent data on different forms of magnesium deficiency and how best to correct it. Presented is the biological role of magnesium in the body of women. We describe the clinical and laboratory signs of magnesium deficiency in gynecological (premenstrual syndrome, menopausal syndrome) and obstetrics (miscarriage, pre-eclampsia) practice. Magnesium drugs reduces the risk of magnesium deficiency in pregnant women and the possibility of threatened abortion and pre-eclampsia. For the correction of magnesium deficiency necessary preparations that have proven high clinical efficacy and good tolerability.